Mining poisonous and harmful gas concentration detection method based on single-point calibration fitting algorithm - BAI JUNWEI; BU DONGWEI; CHENG XIANGQIAN (2022)
The invention is suitable for the technical field of mining poisonous and harmful gas concentration detection, and particularly relates to a mining poisonous and harmful gas concentration detection method based on a single-point calibration fitting algorithm. According to the method, the obtained actual output value of the mine poisonous and harmful gas sensor is subjected to normalization processing to obtain the target data, and the target data and the mine poisonous and harmful gas concentration values corresponding to the four preset reference points are substituted into the target function to obtain the gas concentration value. According to the invention, the concentration of the mining toxic and harmful gas is detected through the single-point calibration fitting algorithm, and the precision of the concentration detection of the mining toxic and harmful gas is improved on the premise that the hardware cost is not increased. 本发明适用于矿用有毒有害气体浓度检测技术领域，特别涉及基于单点标定拟合算法的矿用有毒有害气体浓度检测方法。本发明对获取的矿用有毒有害气体传感器的实际输出值进行归